Em briga de marido e mulher, o estado deve intervir: políticas públicas no estado do Pará que visam prevenir e combater à violência doméstica contra a mulher - SILVA, Kaline Alencar Barros da (2024)
Abstract: The main objective of this work was to analyze the issue of domestic violence against women in the state of Pará and to discuss the main public policies in force in the state aimed at curbing this violence. The methodology used was qualitative, using corresponding bibliographical research on the subject, a report by the Brazilian Public Security Forum and a report by the Public Prosecutor's Office of the State of Pará, referring to violence against women between 2020 and 2023. Although the number of actions aimed at curbing domestic violence in the state has increased in recent years, the rates of domestic violence in the state are still alarming.